Ammonia as an energy vector: Current and future prospects for low-carbon fuel applications in internal combustion engines - Cardoso, João Sousa; Silva, Valter; Rocha, Rodolfo C.; Hall, Matthew J.; Costa, Mário; Eusébio, Daniela (Journal of cleaner production, 2021)
Ammonia and hydrogen carry great potential as carbon-free fuels with promising applications in energy systems. Hydrogen, in particular, has been generating massive expectations as a carbon-free economy enabler, but issues related to storage, distribution, and infrastructure deployment are delaying its full implementation. Ammonia, on the other hand, stands as a highly efficient energy vector delivering high energy density and an established and flexible infrastructure capable of mitigating hydrogen’s key drawbacks. This mature infrastructure together with the possibility of producing ammonia through renewable energy sources triggered an exploring route to the transition of ammonia as the next sustainable fuel solution for power generation. In this regard, the transportation sector as one of the main culprits for carbon emissions can benefit from ammonia-powered internal combustion engines. However, the use of pure ammonia as fuel still presents important constraints leading researchers to develop strategies such as dual-fuel concepts or novel combustion approaches. Therefore, this review covers these issues by delving into the underpinning mechanisms required for developing pure ammonia combustion in internal combustion engines. To do so, fundamentals, technical, environmental, and economic aspects associated with the use of ammonia as a transportation fuel are broadly addressed. While the emphasis is given to pure ammonia and ammonia fuel blends operation, NOx emissions control, current challenges related to the detailed and accurate understanding of the ammonia chemistry, and the lack of high-fidelity numerical models are also deeply discussed on their role into aiding the commercial deployment of this technology.